Mediastinal yolk sac tumor infiltrating the heart - Imaniar, R.; Syahruddin, E.; Soepandi, P.Z.; Putra, A.C.; Nurwidya, F. (Experimental Oncology, 2018)
Background: As a rare tumor, yolk sac tumor is a type of neoplasm that appears like the yolk sac, extraembryonic mesenchyme, and allantois. The mediastinum is the second most frequent area after the gonadal area. Case report: We present an extremely rare case of 15 years old boy with mediastinal yolk sac tumor. The boy came with the chief complaint of swelling of the neck and face. Computed tomography scan of the chest revealed bulky mass with a cystic component that infiltrated the heart. The diagnosis of mediastinal yolk sac tumor was made after core needle biopsy. Histopathologic analysis revealed tumor mass with solid and microcystic structure and pleomorphic nucleus within the tumor cells. Laboratory finding showed elevated serum alpha-fetoprotein level reaching more than 8000 ng/ml. Echocardiography revealed a mass in the right atrium. The patient condition was rapidly deteriorated due to his vena cava superior syndrome. Unfortunately, the patient died two days after diagnosis and we did not have the chance to do the therapy. Conclusion: Mediastinal yolk sac tumor is a rare malignancy that requires comprehensive management. The diagnosis should be made based on histopathological findings with the addition of thoracic computer tomography scan to assess the degree of infiltration to surrounding organ. A life-threatening condition such as vena cava superior syndrome should be assessed promptly to allow for immediate treatment.